PENGARUH DIAMETER MATA BOR TERHADAP PEMAKAIAN DAYA LISTRIK PADA BENCH DRILL IXION BT 25 - Johanes Sulu; Rudy Poeng; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2022)
This research talked about whether using a larger drill bit will decrease or increase electricity usage and whether the drill bit will affect electricity usage on the bench drill IXION BT 25 drill machine. The goal of this research is to analyze the tendency of increasing or decreasing electricity usage on the bench drill IXION BT 25 drill machine based on the relationship graphic between drill bit diameter and power usage based on test results on the drilling process using a coolant and doing some linear regression analysis to obtain the drill bit relationship which affects the electric motor power usage on the bench drill IXION BT 25 drill machine.From the results of the drilling process on the bench drill IXION BT 25 drill machine which has been developed with the coolant, it is found that when the larger diameter of the drill bit is used, the electricity usage will increase. From the results of linear regression analysis, the relationship Y=-0,00088+0,00016X was obtained. It shows that the effect of drill bit diameter on electricity usage from test results on the bench drill IXION BT 25 drill machine which has been developed using a coolant is, every time drill bit diameter increases by 1 mm, the electricity usage increases by 0,00016 KWHKeywords: Â Â Drill Bit, Electric Power Consumption, Bench Drill IXION BT 25 Drill Machine Â